(untitled) (Health Renaissance, 2012)
Background: Despite increasing number of medical schools, there is a limited data about medical students from Nepal. Information about their characteristics and profile will help devise necessary policies and strategies. Objective: To study social, demographic, economic, geographic, educational and psychological attributes of MBBS students. Methodology: From the list of MBBS students of all years/semesters of BPKIHS (2009), every 5th students were enrolled to include 20% of all. After informed written consent, relevant information was collected from the subject by direct interview and recorded in a priory-prepared semi-structured proforma. The investigator MD-psychiatrist clinically assessed their personality traits. Results: A total of 104 MBBS students were enrolled. Majority were male (76, 69%) and single (102, 98%). Average age was 23 years. Most (79, 76%) came from nuclear family, with family’s better education and employment status. Only fewer (18, 17%) were from rural set-ups. Average distance from the institute was 17 hours of road travel. Though many had local supports of relatives and friends, some expressed lack of support. A variety of creative and extracurricular activities were reported. Besides major clinical subjects, other specialties are also the choice for many future Nepali doctors. Among the personality clusters, many had anxious and anancastic (OC) traits. Conclusion: Majority of MBBS students are male, from urban areas, nuclear family with good economic and educational background. They have a range of recreational extracurricular activities and specialties for future career. Many reported anxious and anancastic traits. DOI: http://dx.doi.org/10.3126/hren.v10i3.7134 Health Renaissance; September-December 2012; Vol 10 (No.3);192-197